Influence of Service Quality and Consumer Trust on the Decision to Use EMKL Services at PT Samudera Perdana Selaras Semarang - Suwardi; Annisa Aulia Fitri (Admisi dan Bisnis, 2026)
This study aims to analyze the extent to which service quality and consumer trust influence the decision to use EMKL services, both partially and simultaneously. This study employed a quantitative approach using a saturated sampling technique with 64 respondents. Primary data were collected using questionnaires and observations, while secondary data were obtained through literature review. The instruments used were tested for validity and reliability. Data analysis was performed using multiple linear regression with the classical assumption test, t-test, and f-test. The results indicate that service quality and consumer trust have a positive and significant influence on the decision to use services, both partially and simultaneously. The coefficient of determination value of 0.436 indicates that service quality and consumer trust together contribute 43.6% to the decision to use services, while 56.4% is influenced by other variables not examined in this study.